A Novel Slicing Method for Thin Supercapacitors. Issue 30 (17th May 2016) - Sun, Hao; Fu, Xuemei; Xie, Songlin; Jiang, Yishu; Guan, Guozhen; Wang, Bingjie; Li, Houpu; Peng, Huisheng
Abstract : Thin and flexible supercapacitors with low cost and individual variation are fabricated by a new and efficient slicing method. Tunable output voltage and energy can be realized with a high specific capacitance of 248.8 F g −1 or 150.8 F cm −3, which is well maintained before and after bending.